The Movement of Cimandiri Fault, Sukabumi, West Java: A Vertical Deformation Analysis Using DInSAR-True Vertical Displacement Method - Stevany, Demi; Manessa, Masita Dwi Mandini (Geological Agency, 2024)
If deformation is caused by earthquakes, it is necessary to map the area size and shape. Especially in Indonesia, which is situated within three main tectonic plates, the examination of risks and hazards is vital to establish the right measures for mitigating and minimizing the risk of earthquakes. Remote sensing is one of the best and most renewable methods for mapping deformation occurrences. DInSAR is a remote sensing technique that can be used to analyze deformation. This work employed the DInSAR technique to examine the Sentinel-1 A SLC-IW satellite and to investigate the deformation of the Cimandiri Fault in Palabuhanratu region, Sukabumi. Within one of these active faults, a magnitude of 4 Richter scale earthquake occurred on September 20th, 2022. Comparing satellite photos before and after the earthquake with the DInSAR yielded a large phase difference value centred on the Cimandiri Fault line with a phase range of -3,092 to 3,031. It indicates that the Cimandiri Fault is the earthquake epicentre on September 20th, 2022, in Palabuhanratu. The results of an investigation of the displacement value happening along the line of sight (LOS) fall between 0.105 and 0.672 m. Due to the incidence angle of the picture observation by satellite, the displacement must be adjusted since it is perpendicular to the ellipsoid referred to as the true vertical displacement. The fixed displacement finding of 0.126 to 0.806 m suggests that the region surrounding the Cimandiri Fault has risen. As GCP points, a number of GPS geodetic data points were incorporated from the field near the Bagbagan bridge, which was the site of the active fault. The outcomes demonstrated that the DInSAR true vertical displacement method can be used to determine the surface deformation.